1506-P: Genomic Monitoring of Islet Graft Injury in Type 1 Diabetic Patients after Islet Transplantation - HUSSEINY, MOHAMED I.; COBB, JACOB; ORR, CHRIS; HACKER-STRATTON, JEANNETTE; FOROUHAR, ELENA; EL-SHAHAWY, MOHAMED A.; KANDEEL, FOUAD R. (Diabetes (New York, N.Y.), 2024)
Introduction & Objective: Early detection of islet graft injury after islet transplantation (IT) may allow timely intervention to preserve islet graft health and function. We hypothesized that in response to IT injury, islet beta-cells will release cell-free DNA (cfDNA) into the circulation allowing for early detection of graft injury. Methods: Real-time bidirectional pyrophosphorolysis-activated PCR (Bi-PAP) and methylation-specific PCR (MSP) assays were developed to detect donor cfDNA and beta-cell specific unmethylated insulin DNA in plasma of individuals with type 1 diabetes who received IT. Under approved protocols at the City of Hope National Medical Center, blood samples from type 1 diabetic IT individuals (n=22) were collected before and after the procedure and analyzed using the Bi-PAP and MSP assays. The longitudinal relationships between the metabolic and immunologic parameters and the appearance of donor-specific cfDNA in circulation of individuals after IT were analyzed. Results: All individuals that underwent IT showed donor-specific cfDNA in plasma (by both methods) on day one after the procedure. Donor-specific cfDNA decreased gradually and was no longer detected in the plasma by day 18 post-IT. Insulin independence and less variation in blood glucose levels after IT was associated with minimal to no plasma donor cfDNA during the study period. In contrast, individuals that did not achieve insulin independence, had wide swings in blood glucose, or that had immune activation after IT were found to have increases in donor cfDNA. Conclusion: Donor islet cfDNA persisted in individuals with poorer outcomes after IT. These findings suggest that donor cfDNA may be markers of islet injury after allo-transplantation. It remains to be seen if donor cfDNA levels provide more insights sooner than other techniques currently employed to monitor islet health after transplantation.